Synthesis of the synchronization of general pipeline systems - Ugron, Balázs; Hajdara, Szabolcs; Kozma, László (Acta cybernetica (Szeged), 2005)
The pipeline systems and different subtypes of pipelines are interesting parts of parallel systems in software engineering. That is why it seems to be worth dealing with the possibilities of the specification of the synchronization of these systems. Different methods exist that can be used to synthesize the synchronization of parallel systems based on some kind of specification, but these methods cannot be applied directly for pipeline systems because of some special properties of the pipeline systems and the methods themselves. The method that seems to be the most promising is the method of Attie and Emerson, which is a synthesization method for many similar processes based on a special temporal logic specification. In this paper we give an extension of this method so that the extended method will be able to handle more properties of parallel systems, especially of pipeline systems. We will consider not only linear [8], but general pipeline systems too. Furthermore, we give an abstract synchronization of a general pipeline system.